The Unfolded Protein Response and Membrane Contact Sites: Tethering as a Matter of Life and Death?. (April 2018) - van Vliet, Alexander R.; Sassano, Maria Livia; Agostinis, Patrizia
The endoplasmic reticulum (ER) is the most extensive organelle of the eukaryotic cell and constitutes the major site of protein and lipid synthesis and regulation of intracellular Ca 2+ levels. To exert these functions properly, the ER network is shaped in structurally and functionally distinct domains that dynamically remodel in response to intrinsic and extrinsic cues. Moreover, the ER establishes a tight communication with virtually all organelles of the cell through specific subdomains called membrane contact sites. These contact sites allow preferential, nonvesicular channeling of key biological mediators including lipids and Ca 2+ between organelles and are harnessed by the ER to interface with and coregulate a variety of organellar functions that are vital to maintain homeostasis. When ER homeostasis is lost, a condition that triggers the activation of an evolutionarily conserved pathway called the unfolded protein response (UPR), the ER undergoes rapid remodeling. These dynamic changes in ER morphology are functionally coupled to the modulation or formation of contact sites with key organelles, such as mitochondria and the plasma membrane, which critically regulate cell fate decisions of the ER-stressed cells. Certain components of the UPR have been shown to facilitate the formation of contact sites through various mechanisms including remodeling of the actin cytoskeleton. In this review, we discuss old and emerging evidence linking the UPR machinery to contact site formation in mammalian cells and discuss their important role in cellular homeostasis.